Optimal C:N ratio for the production of red pigments by Monascus ruber - M. Said, Farhan; Brooks, John; Chisti, Yusuf (Springer Netherlands, 2014)
The carbon-to-nitrogen (C:N) ratio in the biomass of microfungi tends to be quite different (e.g. 10–15) compared with the C:N ratio in the red pigments (e.g.[20) of the fungus Monascus ruber. Therefore, determining an optimal C:N ratio in the culture medium for maximizing the production of the pigments is important. A culture medium composition is established for maximizing the production of the red pigment by the fungus M. ruber ICMP 15220 in submerged culture. The highest volumetric productivity of the red pigment was 0.023 AU L-1 h-1 in a batch culture (30 C, initial pH of 6.5) with a defined medium of the following composition (g L-1): glucose (10), monosodium glutamate (MSG) (10), MgSO47H2O (0.5), KH2PO4 (5), K2HPO4 (5), ZnSO47H2O (0.01),FeSO47H2O (0.01), CaCl2 (0.1), MnSO4H2O (0.03). This medium formulation had a C:N mole ratio of 9:1. Under these conditions, the specific growth rate of the fungus was 0.043 h-1 and the peak biomass concentration was 6.7 g L-1 in a 7-day culture. The biomass specific productivity of the red pigment was 1.06 AU g-1 h-1. The best nitrogen source proved to be MSG although four other inorganic nitrogen sources were evaluated.